2020
DOI: 10.3390/nu12051214
|View full text |Cite
|
Sign up to set email alerts
|

Decanal Protects against UVB-Induced Photoaging in Human Dermal Fibroblasts via the cAMP Pathway

Abstract: Solar ultraviolet (UV) radiation is the primary factor of cutaneous aging, resulting in coarse wrinkles and dryness. In this study, we aimed to test whether decanal, an aromatic compound found mainly in citrus fruits, inhibits UVB-mediated photoaging in human dermal fibroblasts and to explore whether its anti-photoaging effect occurs via cyclic adenosine monophosphate (cAMP) signaling. We found that decanal promotes collagen production dose-dependently. Meanwhile, it also increased the intracellular cAMP level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Matrix metalloproteinases (MMPs) are known as collagenase and the UVB-induced expressions of MMP1, 3, and 9 are considered as the dominant cause of decreased collagen in skin ( Kang et al, 2020 ). In cultured dermal fibroblasts, the transcriptional levels of different MMP isoforms, i.e., MMP1a, MMP3, and MMP9, were increased markedly by few folds under UVB irradiation ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) are known as collagenase and the UVB-induced expressions of MMP1, 3, and 9 are considered as the dominant cause of decreased collagen in skin ( Kang et al, 2020 ). In cultured dermal fibroblasts, the transcriptional levels of different MMP isoforms, i.e., MMP1a, MMP3, and MMP9, were increased markedly by few folds under UVB irradiation ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although hyaluronic acid makes up only ~0.1–0.3% of dry skin weight, it can bind up to 1000 times its weight of water [ 44 , 45 , 46 ]. Hyaluronic acid is produced in the plasma membrane by HAS1–3; HAS2 appears to be the dominant isoform in dermal fibroblasts because of the extent to which HAS2 upregulation correlates with an increase in hyaluronic acid secretion [ 47 , 48 , 49 ]. In the present study, β-ionone treatment attenuated dexamethasone-induced suppression of type I procollagen genes and of the HAS2 gene and increased both procollagen and hyaluronic acid contents in human dermal fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…We found that carvone treatment activated the cAMP signaling pathway (Figure 3), which is known to be upregulated in a relatively short time in response to various stimuli [32][33][34]. Although the mechanisms by which carvone raises cAMP concentrations are unknown, it is worth noting that carvone has been identified as a ligand of numerous olfactory receptors (ORs; e.g., OR1A1, OR8B3, and OR5P3, which constitute the largest subfamily of G-protein-coupled receptors) in each OR-transfected HEK293 cell line [35,36].…”
Section: Discussionmentioning
confidence: 90%